2007
DOI: 10.1210/me.2007-0263
|View full text |Cite
|
Sign up to set email alerts
|

Response of Candidate Sex-Determining Genes to Changes in Temperature Reveals Their Involvement in the Molecular Network Underlying Temperature-Dependent Sex Determination

Abstract: Gonadogenesis, the process of forming an ovary or a testis from a bipotential gonad, is critical to the development of sexually reproducing adults. Although the molecular pathway underlying vertebrate gonadogenesis is well characterized in organisms exhibiting genotypic sex determination, it is less well understood in vertebrates whose sex is determined by environmental factors. We examine the response of six candidate sex-determining genes to sex-reversing temperature shifts in a species with temperature-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 62 publications
6
89
2
2
Order By: Relevance
“…Dmrt1 transcript expression in individual embryos was highly temperature dependent between 25 and 33°C, during the sexdetermination period and TSP. The temperature-shift assays showed a rapid response of Dmrt1 to temperature shifts from MPT to FPT or FPT to MPT both in vivo and in vitro, preceding changes in Amh and Sox9, which is consistent with previous reports (Shoemaker-Daly et al, 2010;Shoemaker et al, 2007b). These findings confirm the thermosensitivity of Dmrt1 in T. scripta gonadal cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dmrt1 transcript expression in individual embryos was highly temperature dependent between 25 and 33°C, during the sexdetermination period and TSP. The temperature-shift assays showed a rapid response of Dmrt1 to temperature shifts from MPT to FPT or FPT to MPT both in vivo and in vitro, preceding changes in Amh and Sox9, which is consistent with previous reports (Shoemaker-Daly et al, 2010;Shoemaker et al, 2007b). These findings confirm the thermosensitivity of Dmrt1 in T. scripta gonadal cells.…”
Section: Discussionsupporting
confidence: 91%
“…Some genes (or gene networks) involved in GSD systems have been identified in the gonads of TSD species during the thermosensitive period (TSP), and several of those exhibit temperature-dependent expression patterns prior to gonadal sex differentiation (Shoemaker-Daly et al, 2010;Shoemaker et al, 2007b). The idea that TSD and GSD systems share common genetic components is strongly supported by recent transcriptomes of TSD taxa from the red-eared slider turtle (Czerwinski et al, 2016), the painted turtle (Radhakrishnan et al, 2017) and the alligator (Yatsu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the nuclear localization of SOX9 seems to be essential for its function in male sex determination such that the equilibrium of its nuclear import/export may regulate the repression of female-or the activation of male-specific differentiation [Gasca et al, 2002]. Consistent with the mammalian model, SOX9 expression is upregulated in male embryonic gonads in TSD turtles and crocodilians ( Trachemys scripta [Spotila et al, 1998;Shoemaker et al, 2007a], Lepidochelys olivacea [Moreno-Mendoza et al, 1999;Torres-Maldonado et al, 2001], and alligators [Western et al, 1999b]) but notably, it is upregulated at female-rather than at male-producing temperatures in the TSD leopard gecko Eublepharis macularius [Valleley et al, 2001].…”
Section: Sox9 and Dmrt1mentioning
confidence: 74%
“…While Sox9 is required for sexual differentiation in eutherians by controlling the development of a testis-specific somatic lineage, in other vertebrates the situation is less clear. Although Sox9 expression is sexually dimorphic in chicken, alligator and turtles, male-specific expression is only evident after the expression of anti-Mül-lerian hormone has been initiated (Oreal et al, 1998;Western et al, 1999;Shoemaker et al, 2007), suggesting that activation of Sox9 is not a primary sex-determining gene in these species. In these non-eutherian vertebrates it is suggested that Sox9 acts to control the correct differentiation of the somatic Sertoli cell lineage rather than its specification (e.g., Smith et al, 1999).…”
Section: Discussionmentioning
confidence: 99%